Integrated systems improve soil microclimate, soybean photosynthesis and growth - da Silva, Luciana Maria; Habermann, Eduardo; Costa, Kátia Aparecida de Pinho; Costa, Adriano Carvalho; Silva, João Antônio Gonçalves e; Severiano, Eduardo da Costa; Vilela, Lourival; Silva, Fabiano Guimarães; da Silva, Alessandro Guerra; Marques, Bruno de Souza; Rodrigues, Fabrício; Martinez, Carlos Alberto (Frontiers in Plant Science, 2025)
This study aimed to compare the conventional soybean (Glycine max L.) cultivation method with integrated systems in an Latossolo Vermelho Acriférrico típico and how these systems affect soil cover biomass production, initial nutrient concentration in plant residues, soil respiration and microclimate, as well as soybean growth, physiology and productivity. A comparative analysis of microclimate and soil respiration, plant physiology, and growth was conducted between a conventional soybean monoculture (soybean grown without plant residues on the soil from the previous crop) and soybean grown in soil containing maize residues. Additionally, experiments were conducted to evaluate the effect of monocultures and previous integration between maize, three cultivars of Panicum maximum (Zuri, Tamani, and Quênia guinea grass) and Pigeon pea (Cajanus cajan cv. BRS Mandarim) on soil health, physiological aspects, and soybean production. Our results indicated that all cultivars of Panicum maximum can be used in integrated systems. The triple consortium resulted in greater production of ground cover biomass and a higher concentration of nitrogen, phosphorus, potassium and sulphur, which contributed to lower soil temperature and greater humidity, without a concomitant increase in soil respiration. Consequently, soybeans grown in the resulting integrated systems cover biomass showed a higher net photosynthesis rate and increased leaf chlorophyll index, resulting in taller plants, with higher above-ground biomass production and 21.0% and a 36.8% increase in grain yield when compared to soybean cultivated on maize biomass and on soil without cover residue, respectively. The data presented in this study demonstrated that integrated systems, with the presence of grasses and legumes, improve soil climatic conditions and nutrient availability, enhancing soybean physiology and productivity characteristics, thus contributing to the sustainability of agricultural production, even in the short term. Further long-term research is strongly recommended.